It is here that we've come to live: imagined representations of Delft South as a post-apartheid township - Zono, Baxolele (School of Architecture, Planning and Geomatics, 2018)
This research dissertation employed critical research approach and postcolonial theory to investigate and expose the ways in which post-apartheid township space has been imagined and created for the black lives that twenty-one years ago emerged from the long dry season of apartheid hegemony. The dissertation used Delft South township as a case study for the reason that it carries the notion of a post-apartheid township and as a result it has been imagined as such. In its creation as a 'new' kind of township, Delft South was stipulated in terms of section 3 (1) chapter 1 of the Less Formal Township Act, 1991 and imagined through the 1994 Reconstruction and Development Programme and as well in the 1994 Housing White Paper and later expanded in the 2004 'Breaking New Ground': Comprehensive Plan for Housing. The development of housing in Delft South was adopted in 1994, followed by its physical construction in 1995. Through studying this township, it became apparent that the ways in which the post-apartheid township has been created for the black poor did not challenge the notion of township, as we know it, under the apartheid racial regime. Paradoxically, it has been found that the post-apartheid neoliberalised housing policies that promotes inclusion has exercised exclusion in the housing development and provision of low income houses to the urban black poor. Moreover, in reading what the post-apartheid statecraft has created (making of place) it became clear that the post-apartheid state to follow Achille Mbembe is not 'an economy of signs in which power is mirrored and imagined self-reflectively.' But that which is stammering to find its way out from the world of masks, of repetition to the recreation of a new community of life, of collective dreams and healing. Therefore, the creation of Delft South like any other post-apartheid township without doubt, has come to epitomize the manner in which the post-apartheid state asserted itself in the making of place and also, how it has come to create itself defectively after apartheid.